Los derechos de los niños, niñas y adolescentes Son irrenunciables, por lo que no es admisible la Transacción por parte de los padres, curadores o Tutores de los menores, de quienes tenga la Patria potestad, tratándose de delitos sexuales De que hayan sido víctimas los menores, por lo que El código penal ecuatoriano, debe contener Sanciones para quienes incurran en estas Conductas - Manzanilla Torres, José Kleber (2014)
This legal research falls within the academic problems of criminal law, in particular in the Ecuadorian Penal Code, research that meets the requirements laid down in Regulation Academic Board of the National University of Loja, which regulates the relevance of the study legal aspects inherent in investigative matters Positive law, to opt for law degree from the Courts of the Republic of Ecuador. It is proposed to further demonstrate the need for effective protection required the state to minors, children and adolescents who have been victims of sexual offenses, and whose parents or guardians or who are responsible for the care and protection of children, having instituted criminal proceedings against those responsible for the commission of that offense, for economic reasons, familiarity, family or any other reason agree agree-transaction-so that those responsible do not comply with the punishment. The problem on which this research focuses, is related to sex crimes, sexual abuse, sexual harassment, rape and other committed against minors. The rights of children and adolescents in principle be waived if a teenager was the victim of a sexual offense, a behavior that the Ecuadorian Penal Code criminalizes sexual offense, which can be rape, sexual abuse, sexual harassment, crimes that threaten the physical, psychological and sexual integrity of minors guarantees established in the Constitution of the Republic of Ecuador, thus being public offenses not applicable transaction or any agreement preventing the course of justice. The rights of children and adolescents are recognized worldwide by the Declaration of the Rights of the Child and the Convention on the Rights of the Child. As our Constitution has also seen fit to establish in its articles such protection, since children and adolescents are a priority group for the state. Other factors have also contributed to this group deserves special attention by the government, such as migration, child exploitation, physical abuse and verbal. Sex crimes are crimes of public action, these actions meet the Public Ministry, through the Fiscal Agentas sex crimes, actions are initiated ex officio if becomes aware of these tax the commission of these crimes, denouncing legal guardians of the minor who suffered the attack, so it is not possible that you can swindle to avoid the course of justice and punishment of those responsible and, it is considered heinous crimes, causing alarm society and whose severity increases with younger age. So it is necessary to reform the Code of Childhood and Adolescence, incorporating provisions prohibiting a possible transaction attempting the child's parents, your guardian, or those exercising parental authority, transactional action that should be rejected by the respective judges, transaction submitted with any denomination. The problem is that there are cases in which parents, guardians, or those with the power of the lower country, propose a transaction so that the head of the sex crimes go unpunished, we propose and having the ability to accept or not the Judge of Criminal Guarantees concerned that in general not accepted but there will be some. if accepted, the transaction involves money involved, that the perpetrator of the crime has to cover false statements within the procedure that exempt or mitigate the responsibility of the author of the criminal fact accepted.